The Effects of Price, Brand Image, and Product Quality on Customer Satisfaction and Customer Value - Setiadi, Zikri Wildan; Sari, Novita (LifeSciFi, 2026)
The highly competitive telecommunications industry poses customer retention challenges, due to price wars lowering average revenue per user, limited marketing of premium products, and network instability affecting digital experiences. This study examines the effects of price, brand image, and product quality on customer satisfaction and value within a single integrated model. A quantitative survey of customers was conducted, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The data analysis results indicate that the price variable does not have a significant effect on either customer satisfaction or customer value. In contrast, the brand image variable shows a strong positive effect on both customer satisfaction and customer value. Product quality is found to be the most dominant predictor of customer value directly, although it does not have a significant effect on customer satisfaction. Customer satisfaction mediates the effect of price on value, whereas its mediation for brand image and product quality is not significant. These findings suggest that enhancing product quality, strengthening brand image, and optimizing pricing can effectively increase customer satisfaction and customer value. This study provides both theoretical and managerial insights for improving customer value in the telecommunications industry.